Irregularity Invariants for Chemical Structures Used in the Treatment of COVID-19 - Virk, Abaid ur Rehman; Bilal, Shams; Hamid, Khalid (Scientific Inquiry and Review, 2020)
The world is going through the pandemic of COVID-19. Remdesivir, chloroquine, hydroxychloroquine and theaflavin are some drugs currently in use for the treatment of the COVID-19 patients. This manuscript aims to compute the irregularity measures for these chemical structures. We believe that our results can be utilized to improve the capacity of these chemical structures. Copyright(c) The Authors